The Effectiveness of Google Meet on Mathematics Problem Solving Ability of Class XI Students - Proborini, Ellen; Ulfa, Uli (IndoMath: Indonesia Mathematics Education, 2022)
The purpose of this study was to determine the effectiveness of Google Meet on students' mathematical problem solving abilities. The population of this study were students of class XI SMK Tunas Harapan Pati for the 2020/2021 academic year. This study uses a quantitative research method with an experimental method, where the treatment is only carried out once in the sample class which is estimated to be able to have an influence on learning outcomes. Data collection techniques using documentation and test methods. The results showed that the problem solving ability of students was more effective if it was done using google meet in learning mathematics on the opportunity material for students of class XI APL SMK Tunas Harapan Pati. This is evidenced by the increase in value from 669.57 to 78.